(untitled) (Damascus University Journal for engineering sciences, 2021)
One of the most encouraging uses of parallel systems is to reduce the execution time of the calculation of the programs. The implementation time for the sub-program depends on several factors including the structure of the implementation platform ,interpreter, the operating system, the parallel programming environment, and model used. Even the characteristics of the applied software as a reference to the program’s memory and the dependencies between the calculations that will actually run. All these factors must be taken into account when the parallel software is developed, though it is very hard to combine all these factors together. In order to implement the development and analysis of the parallel software, it is often used to measure performance or effectiveness which will used to analyze and compare the different versions of the parallel software